Strategi Corporate Social Responsibility dan Modal Intelektual: Pengaruhnya terhadap Nilai Perusahaan dan Kinerja Keuangan - Wahyudi, Wahyudi (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The development of the modern business world requires companies to not only focus on achieving financial profits, but also to make positive contributions to society and the surrounding environment. This research aims to investigate the influence of Corporate Social Responsibility and Intellectual Capital strategies on company value and financial performance. Thus, this research aims to provide a better understanding of the importance of this strategy in the context of corporate management. This research was carried out using an associative approach and followed the steps of quantitative research work. The data analysis process was carried out using a panel data linear regression test. The results of the analysis show that effective implementation of CSR strategies and good management of Intellectual Capital have a positive influence on company value and financial performance. This indicates that companies that prioritize these aspects tend to experience improvements in their competitiveness and financial performance.